Examining organizational drivers of sustainability: A study of Vocational Education Institutions in Indonesia - Wanto; Masydzulhak Djamil; Indra Siswanti; Dudi Permana (Social Sciences and Humanities Open)
This paper investigates the impact of organizational dynamics on sustainable performance, with a particular focus on the Center for the Development and Quality Assurance of Vocational Education in Indonesia. The study explores three primary independent variables: Organizational Ecology (OEC), Organizational Efficiency (OEF), and Social Capital (SC), along with the role of the Green Management System (GMS) in influencing Sustainable Performance (SP). The findings reveal that both Organizational Ecology and Organizational Efficiency significantly enhance Sustainable Performance. Organizational Ecology, which includes the integration of ecological initiatives and dynamic organizational practices, shows a strong positive effect on sustainable outcomes. This highlights the critical role of environmental stewardship within organizations. Similarly, Organizational Efficiency, which focuses on optimizing operations and managing resources effectively, is a key driver of sustainable success. Social Capital also contributes positively to Sustainable Performance, though its impact is less pronounced compared to Organizational Ecology and Efficiency. This indicates the importance of fostering strong interpersonal relationships and collaborative environments within organizations to support sustainability goals. Conversely, the influence of the Green Management System on Sustainable Performance is found to be weak and statistically insignificant. This suggests potential limitations in the direct contributions of Green Management Systems to overall sustainable performance metrics within the organization. These insights offer valuable guidance for organizations aiming to enhance their sustainability strategies. By prioritizing efforts to improve organizational ecology, boost operational efficiency, and build social capital, organizations can better align with sustainable development goals, promoting long-term environmental and organizational resilience.